SEPSIS - Yulson Yulson; Ade Ariadi (Nusantara Hasana Journal, 2026)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection. It remains one of the leading causes of morbidity and mortality worldwide, particularly among patients admitted to intensive care units. Sepsis can progress to septic shock, characterized by persistent hypotension, impaired tissue perfusion, and multiple organ failure if not promptly recognized and treated. Early diagnosis requires comprehensive clinical assessment, laboratory evaluation, and the use of screening tools such as the Sequential Organ Failure Assessment (SOFA) and quick SOFA (qSOFA) scores. The management of sepsis includes early fluid resuscitation, timely administration of empiric antibiotics, source control of infection, hemodynamic support, and continuous monitoring of organ function. Numerous studies have demonstrated that early recognition and adherence to evidence-based clinical guidelines significantly reduce mortality rates and improve patient outcomes. Therefore, increasing healthcare professionals’ awareness, implementing effective sepsis protocols, and promoting a multidisciplinary approach are essential to enhancing the quality of care and patient safety in sepsis management.